Work incentives and the efficiency of tax-transfer reforms under constrained labor supply - Benjamin Fischer; Robin Jessen; Viktor Steiner (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
Using information on desired and actual hours of work, we formulate a discrete choice model of constrained labor supply, where involuntary unemployment as well as over- and underemployment are modelled in a theoretically consistent way. Using data from the German Socio-Economic Panel (SOEP) and the microsimulation model STSM, we find that estimated own wage elasticities in the constrained model are substantially smaller than those obtained from the conventional one using only actual hours. We apply the model to evaluate two hypothetical budget neutral reforms of the German tax-transfer system. Both are aimed at improving labor supply incentives for the working poor, but differ regarding the impact of upward and downward constraints on labor supply reactions. The first increases transfer withdrawal rates, making working few hours unattractive, and redistributes to the lower middle class. The second reform increases taxes and redistributes to the lower middle class. We propose a simple measures to capture the redistributive trade-off of reforms. We find that the first reform is desirable with equal welfare weights, but, with labor market constraints, the effects are limited. In contrast, the second reform is only desirable if the social planner has substantial redistributive taste.
Keywords: J22; 330; Tax-benefit systems; Household labor supply; Labor market constraints; Involuntary unemployment; equity-efficiency tradeoff